A Perspective on Merging databases for bibliometric analysis - Dagli, Namrata; Kurian, Jestina Rachel; Haque, Mainul (Bangladesh Journal of Medical Science, 2025)
Abstract not available BJMS, Vol. 24 No. 04 October’25 Page : 1025-1028